Community Forest Management in Nigeria: A Case of Local Empowerment and Environmental Management Project (Leemp) In Adamawa State (Journal of Tropical Resources and Sustainable Science (JTRSS), 2015)
Deforestation continuous to be a wide spread problem in rural areas of developing countries. Conventional “top down” approach has proved fundamentally limited in their ability to promote the culture of forest conservation in the world over. Inco-prorating the community based forest and community based natural resources management in rural development strategies seems to be the best approach to conserve forest area. This paper provides a case of community forest management by rural communities in rural areas of Nigeria. Based on the experience of the Local Empowerment and Environmental Management Project (LEEMP) in Adamawa State of Nigeria, this paper discussed the achievement and challenges in implementing community based forest management in the rural areas. Information used in this paper is based a preliminary study in evolving interviews with officials of the implementation agencies of LEEMP and a few participants of the projects in Adamawa state. Under LEEMP the priorities include the empowerment of local people to manage the community based forest and community based natural resources conservation in their areas. The project aim for the effective management of renewable forest resources, (vegetation), minimizing depletion of non-renewable forest resources (wild life), minimise forest pollution and its attendants negative impacts.(bush burning), as well as to decentralize the responsibity for managing forest resources. This study found that LEEMP helps to bring grass root citizen contribution to the objectives of sustainable natural resources management and community wellbeing collectively. There exist a strong link between the rural poverty and the deforestation and forest management through community empowerment did show some improvement both to the resource conservation and improvement to the livelihood of the communities. However there were many challenges encounter in the process implementationinclude non-inclusive of stake holders because of social class or due to political affiliation, while projects are not evenly distributed among communities of serious need, others are un involve and ill-informed in terms of decision and actions, and lack of conservation culture, among communities. This paper implies that effective incorporation of forest management in rural development strategies should focus more attention to collective action, which ties the community on values, cultures, and economics benefits into the ecological project, with balancing the aim of sustaining the environment and poverty alleviation.
Keywords: Community; forest management; deforestation; rural poverty